2010
DOI: 10.1038/nchembio.406
|View full text |Cite
|
Sign up to set email alerts
|

n→π* interactions in proteins

Abstract: Hydrogen bonds between backbone amides are common in folded proteins. Here, we show that an intimate interaction between backbone amides likewise arises from the delocalization of a lone pair of electrons (n) from an oxygen atom to the antibonding orbital (π*) of the subsequent carbonyl group. Natural bond orbital analysis predicted significant n→π* interactions in certain regions of the Ramachandran plot. These predictions were validated by a statistical analysis of a large, non-redundant subset of protein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
456
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(478 citation statements)
references
References 48 publications
18
456
4
Order By: Relevance
“…Another possible stabilizing factor is the n→π* interaction between adjacent peptide bonds (44). Simulations have suggested that dipole-dipole interactions between peptide bonds, which correspond to the quantum mechanical n→π* interactions, can explain the self-association of polyglycine peptides (25,45).…”
Section: Significancementioning
confidence: 99%
“…Another possible stabilizing factor is the n→π* interaction between adjacent peptide bonds (44). Simulations have suggested that dipole-dipole interactions between peptide bonds, which correspond to the quantum mechanical n→π* interactions, can explain the self-association of polyglycine peptides (25,45).…”
Section: Significancementioning
confidence: 99%
“…This interaction, which is reminiscent of the Bü rgi-Dunitz trajectory for nucleophilic addition to a carbonyl group, [17][18][19] induces a short contact between the nucleophile and the carbonyl carbon in which the van der Waals surfaces of the nucleophile and carbon interpenetrate. 10,12 This interaction has been identified in small molecules, such as c-aminobutyric acid 20 and aspirin, 21 and larger molecular systems, including peptides, 16 peptoids, 22,23 and proteins, 8 and could have directed the prebiotic genesis of ribonucleotides. 24 We suspected that the electron-deficient carbonyl carbon of the imidazolidinone ring could interact with a proximal nucleophilic donor.…”
Section: Introductionmentioning
confidence: 99%
“…8 Such an interaction, which we refer to as an ''n!p* interaction,'' 9-16 involves delocalization of the electron lone pair (n) of the nucleophilic donor into the antibonding orbital (p*) of the carbonyl group acceptor. This interaction, which is reminiscent of the Bü rgi-Dunitz trajectory for nucleophilic addition to a carbonyl group, [17][18][19] induces a short contact between the nucleophile and the carbonyl carbon in which the van der Waals surfaces of the nucleophile and carbon interpenetrate.…”
Section: Introductionmentioning
confidence: 99%
“…We found n!p* interactions in 31% of residue-steps, which agrees with the average of 34% found previously. 12 Ten percentage of the Ca-H groups made hydrogen bonds to C@O groups, which is in line with the proportion identified by Derewenda et al 5 Turning to CH X bonds (donated by side-chain CH 3 , CH 2 , or CH groups), we find that 10% of all such available groups in the dataset formed these weak hydrogen bonds, a much reduced proportion compared with the 36% found by Yesselman et al 9 However, this discrepancy can probably be explained in that our analysis only considers hydrogen bonds accepted by main-chain C@O groups and not other hydrogen bond acceptors.…”
Section: Prevalence Of "Weaker" Interactionsmentioning
confidence: 99%
“…2 In addition, weaker donor groups such as Ca-H and methyl-H are also possible contributors to protein stability. [5][6][7][8][9] More specifically, other hydrogen-bond-like, NCIs have been implicated, including the n!p* interaction [10][11][12] and methyl-p interactions. 13,14 These particular interactions are much weaker than canonical hydrogen bonds: the latter are typically worth 3-10 kcal/ mol 15,16 ; whereas, n!p* interactions are estimated at 0.7-1.2 kcal/mol, 10,16 and methyl-p interactions at 0.9-1.5 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%